The Urgency of Bajo Traditional Law as a Form of Law Enforcement Against the Performers of the Samenleven Delic - Lusiana Margareth Tijow; Hoiruddin Hasibuan; Hayat Hayat (IAIN Manado, 2021)
Life in Indonesia does not recognize Samenleven's relationship because the rules of law and religion do not justify it, but there are still many things like that in Bajo Village. Bajo customary law includes the Bajo Customary Institution. In this institution, its existence helps the village government develop and regulate matters relating to local customs and solving problems regarding adultery, namely Samen Leven. This paper describes how customary law can be used as a law enforcement instrument to resolve the Samenleven offense. Semenleven is living together between a man and a woman without a legal marriage bond. This research uses the type of empirical normative research. The data types used are primary and secondary data sources using several approaches. The results show that the use of Bajo customary law, as a form of law enforcement against the perpetrators of the Samen Leven offense, will create a bargaining justice where customary law is used as the first route in resolving a conflict between victims, perpetrators, and the community. The consequence is that the perpetrator must admit that he has been guilty and is willing to take responsibility for his mistake following applicable customs. The Bajo Customary Council uses customary law as a reference to resolve any problems that occur in Bajo Village, Tilamuta District, namely customary law by deliberation/mediation.